Women Language Features used by Bella Swan in Twilight Movie - Gabriella Kristina Handayani; Endar Rachmawaty Linuwih (e-LinguaTera, 2023)
This study aims to identify the types and functions of women language features used by Bella Swan in Twilight movie. The design of the study is descriptive qualitative. The data were taken from the utterances of Bella Swan, then analyzed using Lakoff’s theory. The study results discovered eight types of women language features from Bella Swan's utterances: lexical hedges or fillers, tag question, rising intonation, intensifier, hypercorrect grammar, superpolite form, avoidance of strong swear words, and emphatic stress. The most frequent women language features used by Bella Swan was lexical hedges or fillers. The researcher identified 14 functions of women language features used by Bella Swan. The dominant functions of women language features were to indicate uncertainty and lack of confidence, wrap up the idea, denote hesitancy and make the sentence less assertive, and express slight surprise and agreement.